ECONOMIC REVIEW OF BALI CATTLE CARCASS PERCENTAGE BASED ON SLAUGHTERED LIVESTOCK ORIGIN IN MAMBAL ANIMALS SLAUGHTERHOUSE, BADUNG BALI - yuniastika, devinda; Gelgel, Ketut Tono Pasek; Suardana, Ida Bagus Kade (Buletin Veteriner Udayana, 2020)
Bali cattle are known to have a high percentage of carcasses. This study aims to determine the percentage of bali cattle carcasses from highland and lowland areas that were slaughtered in RPH Mambal Abiansemal district, Badung regency, Bali province, and to find out the selling price of carcasses from both regions. This study used 56 bali cattle from Bangli and Gianyar regencies. Data on the percentage of carcass based on animal origin were analyzed using Independent Samples T-Test to see whether there were differences. The relationship between life weight and carcass weight of Bali cattle and the total selling price is used by power regression analysis (Sampurna, 2012). The results showed a higher percentage of the carcass in Bangli Regency, resulting in higher and more profitable selling.